Pengaruh Harga dan Kualitas Pelayanan terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan J&T Express Babelan - Rizky Edi Nurdiansyah; Yayan Hendayana; Ari Sulistyowati; Ridwan Ridwan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. This research aims to find out how much influence price and service quality have on customer loyalty through J&T Express Babelan customer satisfaction. The population in this research is all J&T Express Babelan customers. This research uses quantitative methods. Data was collected through distributing questionnaires to 112 respondents. This sampling technique uses a purposive sampling method. The results of this research show that the price and service quality variables have a positive and significant effect on J&T Express Babelan customer satisfaction, the price and service quality variables have a positive and significant effect on J&T Express Babelan customer loyalty, the customer satisfaction variable has a positive and significant effect on J&T Express Babelan customer loyalty , the price and service quality variables have a positive and significant effect on customer loyalty through J&T Express Babelan customer satisfaction.